Evaluasi Program MBKM (Merdeka Belajar Kampus Merdeka) pada Perguran Tinggi dengan Model CIPP (Context, Input, Process, and Product) - Febriyanti, Chatarina; Kencanawaty, Gita; Irawan, Ari (SAP (Susunan Artikel Pendidikan), 2024)
The purpose of this study is to provide recommendations for the improvement of the MBKM program, which has been facing challenges at the program level. MBKM is a great program for students to develop their competencies and skills so that they can meet the qualifications of DUDI upon graduation. This study used a mixed method, which involved a literature review and discussions and interviews with program managers, lecturers, and students regarding the implementation of MBKM to date. The results of the study showed an increase in the number of students participating in the MBKM program each year. Students felt the benefits of participating in the MBKM program to gain experience, competencies, soft and hard skills. However, there are still some challenges related to the implementation of the conversion of course credits, the implementation time, and the limited program quota. These issues should be considered so that the program can be improved in the future, with careful planning, implementation, and evaluation.